Entrapment of an EGFR inhibitor into nanostructured lipid carriers (NLC) improves its antitumor activity against human hepatocarcinoma cells - Bondì, Maria Luisa (BioMed Central, 2014)
BACKGROUND: In hepatocellular carcinoma (HCC), different signaling pathways are de-regulated, and among them, the expression of the epidermal growth factor receptor (EGFR). Tyrphostin AG-1478 is a lipophilic low molecular weight inhibitor of EGFR, preferentially acting on liver tumor cells. In order to overcome its poor drug solubility and thus improving its anticancer activity, it was entrapped into nanostructured lipid carriers (NLC) by using safe ingredients for parenteral delivery. RESULTS: Nanostructured lipid carriers (NLC) carrying tyrphostin AG-1478 were prepared by using the nanoprecipitation method and different matrix compositions. The best system in terms of mean size, PDI, zeta potential, drug loading and release profile was chosen to evaluate the anti-proliferative effect of drug-loaded NLC versus free drug on human hepatocellular carcinoma HA22T/VGH cells. CONCLUSIONS: Thanks to the entrapment into NLC systems, tyrphostin AG-1478 shows an enhanced in vitro anti-tumor activity compared to free drug. These finding raises hope of future drug delivery strategy of tyrphostin AG-1478 -loaded NLC targeted to the liver for the HCC treatment.